Literature Review; The Effect of Buerger Allen Exercise on Ankle Brachial Index (ABI) Values in Diabetes Mellitus Type 2 Patients; Literature Review - Carmitha Nareswari Basmallah; Imroatul Farida; Fatin Lailatul Badriyah (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
Introduction: Patients with Diabetes Mellitus type 2  tend to have ABI values lower than the normal range due to lack of physical exercise and uncontrolled hyperglycemia. This needs to be prevented through joint movement exercises with the Buerger Allen exercise which can increase blood perfusion in the lower extremities so that there is an increase in the value of the ankle-brachial index (ABI). Objective: This study aims to determine the effect of Buerger Allen exercise on the value of the ankle-brachial index (ABI) in patients with Diabetes Mellitus type 2 based on a review of research journals. Methods: This study uses a literature review method. Search literature using 5 databases, namely Portal Garuda, Sinta, ProQuest, Scopus, and Google Scholar with keywords according to MeSH, namely "Buerger Allen Exercise", "Ankle Brachial Index", and "Diabetes Mellitus Type 2". The PICOS framework was used to adjust the inclusion criteria which were divided into 5 English journals and 5 Indonesian journals and then analyzed narratively based on similarity analysis. Results: The findings of the ten journals stated that the Buerger Allen exercise had a significant effect on the value of the ankle-brachial index (ABI). Discussion: Buerger Allen exercise is a physical exercise to improve foot peripheral perfusion that can increase the value of the ankle-brachial index in type 2 DM patients. Conclusion: Buerger Allen exercise has a significant effect on increasing the ankle-brachial index (ABI) score so that it can be used as a reference source for standard operating procedures and nursing interventions.Keywords: Buerger Allen; Exercise; Ankle Brachial Index; Diabetes Mellitus